1982
DOI: 10.1111/j.1471-4159.1982.tb12567.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Variables Influencing the Supply of Tryptophan to the Brain

Abstract: The relations of plasma concentrations of substances claimed to influence brain tryptophan concentration (total tryptophan, free tryptophan, large neutral amino acids) with the concentrations of tryptophan, 5‐hydroxytryptamine (5‐HT), and 5‐hydroxyindoleacetic acid (5‐HIAA) in the forebrain were investigated in rats of different ages (from 8 days to 16 months after birth). In brain, tryptophan fell by 46%, whereas 5‐HT rose by 20% between 8 and 40/42 days after birth. Thereafter, the levels of both tryptophan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…The pattern of changes in 5-HIAA content in the HPOA throughout postnatal development, with a maximum around day 20 (table I), agrees with previously reported patterns from 'forebrain' or whole brain [6,45]. However, the abrupt increase in the content of 5-HT in the HPOA between days 12 and 20 compared to the much more steady pattern in the M R (table I) was not reported in forebrain by Bourgoin et al [6] or in whole brain by Santa et al [45].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The pattern of changes in 5-HIAA content in the HPOA throughout postnatal development, with a maximum around day 20 (table I), agrees with previously reported patterns from 'forebrain' or whole brain [6,45]. However, the abrupt increase in the content of 5-HT in the HPOA between days 12 and 20 compared to the much more steady pattern in the M R (table I) was not reported in forebrain by Bourgoin et al [6] or in whole brain by Santa et al [45].…”
Section: Discussionsupporting
confidence: 80%
“…However, the abrupt increase in the content of 5-HT in the HPOA between days 12 and 20 compared to the much more steady pattern in the M R (table I) was not reported in forebrain by Bourgoin et al [6] or in whole brain by Santa et al [45]. In contrast to the raphe nuclei, maturation of 5-HT systems in the H PO A is not well advanced at birth and, in terms of innervation and terminal formation, extends throughout the first 3 postnatal weeks [35,36], The development of the 5-HT neuronal net work within the HPOA probably contributes to the increas ing 5-HT concentrations in the HPOA during the first 3 postnatal weeks (table I).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…De velopmental changes in the blood-brain bar rier (BBB) might play a role here, since there is some evidence for changes with age in the cerebral influx rate of large neutral amino acids from physiological blood levels. Re sults obtained with the most frequently em ployed approach, the rapid intracarotid in jection technique of Oldendorf [8], showed that the brain uptake index (BUI) for trypto phan in rabbits decreases during the first 28 postnatal days [9], In rats, the BUI for tryp tophan was reported to be higher in the late suckling period than in adulthood [10]. Whether there is also a change early on is not known, since the 19th postnatal day was the youngest age at which the BUI of an amino acid (that of tryptophan and valine) has been determined in rats [10,11], Adaptation of the Oldendorf method [8] to younger rats was, therefore, one of our objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Re sults obtained with the most frequently em ployed approach, the rapid intracarotid in jection technique of Oldendorf [8], showed that the brain uptake index (BUI) for trypto phan in rabbits decreases during the first 28 postnatal days [9], In rats, the BUI for tryp tophan was reported to be higher in the late suckling period than in adulthood [10]. Whether there is also a change early on is not known, since the 19th postnatal day was the youngest age at which the BUI of an amino acid (that of tryptophan and valine) has been determined in rats [10,11], Adaptation of the Oldendorf method [8] to younger rats was, therefore, one of our objectives. This paper presents results indicating that the BUI for Phe declines appreciably during the first 3 weeks of age, and discusses develop mental changes in the BBB which might con tribute to the coincident decrease of Phe accumulation in the brain of hyperphenylal aninémie animals.…”
Section: Introductionmentioning
confidence: 99%